Summaries of Final Papers Graduation for Choosing Bachelor's Degree in Library and Information Science, 1998-1999 - Hidalgo Gamboa, Gabriela (1999)
This article contains summaries of final papers from Graduation to Opt for the Bachelor's Degree in Library and Documentation, 1998-1999.